2021
DOI: 10.2147/prom.s304672
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Outcome and Risk Factors of Cesarean Delivery Among Pregnant Women Utilizing Delivery Services at Selected Public Health Institutions, Oromia Region, South West Ethiopia

Abstract: Background: Approximately 10% of deliveries are considered as high risk, which may require cesarean section. Besides, a rise in cesarean section delivery is a real public health concern; cesareans are costly and carry 8-12 and 8 times higher feto-maternal morbidity and mortality, respectively, as compared to vaginal delivery. Like in other countries where unnecessary cesarean delivery is performed, it is also rising in our country, posing potential risk to the mothers and their newborns. Objective: To assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
1
4
2
Order By: Relevance
“…Cesarean section facilities are either not available or too far away for these women which render them to visit health facility after prolonged labor or after they experience at least one of obstetric complications which exposes the mother for complications. This finding was supported by previous studies done in Yirgalem and Oromia region, Ethiopia, which showed that rural women were 3 and 1.3 times more vulnerable for complication respectively [ 14 , 17 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Cesarean section facilities are either not available or too far away for these women which render them to visit health facility after prolonged labor or after they experience at least one of obstetric complications which exposes the mother for complications. This finding was supported by previous studies done in Yirgalem and Oromia region, Ethiopia, which showed that rural women were 3 and 1.3 times more vulnerable for complication respectively [ 14 , 17 ].…”
Section: Discussionsupporting
confidence: 85%
“…The overall maternal complications were 44.04% (CI 95% 39.6–48.5). This finding is higher compared to other studies conducted in Debre Birhan (16.5%) [ 16 ], Jimma (28%) [ 12 ], Finote Selam (28%) [ 13 ], Oromia (20.5%) [ 14 ], Tigray (19.3%) [ 15 ], Yirgalem (30.1%) [ 17 ] and Arbaminch (38.2%) [ 18 ]. It is also higher than the finding in Germany (10.5%) [ 19 ], But it was relatively lower than the finding in Hawassa which was found to be 56% [ 20 ].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Statistical Package for Social Science (SPSS) (version 23, IBM Corp. Armonk, N.Y., United States) was used in analyzing data. 16 Univariate analysis was used to assess the association between patients’ sociodemographic, microbiological, and clinical characteristics with unsuccessful treatment outcomes. To identify the ultimate predictors of unsatisfactory treatment outcomes, multiple logistic regression analysis was used to examine statistically significant factors in univariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal anesthesia is superior to General Anesthesia because, it has universal acceptance. But patients in many countries, including Ethiopia, still prefer GA and are afraid of regional block [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%